Brief report: Identifying defenders of peer victimization. (June 2016) - Meter, Diana J.; Card, Noel A.
Abstract: Betweenness centrality quantifies the amount of network flow that a network member controls as hypothetical traffic passes between network members. Those with high betweenness centrality within the peer social network based on nominations of liking may be especially important connectors between individuals who do not like each other. This study tested the hypothesis that individuals' betweenness centrality would predict their defending of victimized peers. After controlling for popularity, perception of being liked, and defenders' victimization, betweenness centrality predicted defending. Those found to be connectors within the peer group were more likely to be those who defend peer victims. This investigation showed that analysis of betweenness centrality is a viable way to identify potential defenders in research and also those who could potentially act as mediators.